2016
DOI: 10.3389/fpls.2016.01488
|View full text |Cite
|
Sign up to set email alerts
|

The ALMT Family of Organic Acid Transporters in Plants and Their Involvement in Detoxification and Nutrient Security

Abstract: About a decade ago, members of a new protein family of anion channels were discovered on the basis of their ability to confer on plants the tolerance toward toxic aluminum ions in the soil. The efflux of Al3+-chelating malate anions through these channels is stimulated by external Al3+ ions. This feature of a few proteins determined the name of the entire protein family as Aluminum-activated Malate Transporters (ALMT). Meanwhile, after several years of research, it is known that the physiological roles of ALMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 90 publications
(157 reference statements)
3
88
0
Order By: Relevance
“…Ouma et al [94] found that the nutrient culture screening for Al toxicity can predict field selection under Al toxic soils with an accuracy of 24 to 35%, depending on the saturation level of Al in a particular soil and the level of available phosphorus. Under low soil pH, Al ions tend to form highly stable complexes with phosphorus [102]. Under these conditions, maize cultivars with high P use efficiency have a good acid soil tolerance capacity.…”
Section: Conventional Breeding Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ouma et al [94] found that the nutrient culture screening for Al toxicity can predict field selection under Al toxic soils with an accuracy of 24 to 35%, depending on the saturation level of Al in a particular soil and the level of available phosphorus. Under low soil pH, Al ions tend to form highly stable complexes with phosphorus [102]. Under these conditions, maize cultivars with high P use efficiency have a good acid soil tolerance capacity.…”
Section: Conventional Breeding Methodsmentioning
confidence: 99%
“…Froese and Carter [132] found that the positive allele of marker wmc331 linked to ALMT1 was not widely present in the winter wheat germplasm used in their study but was present only in the most tolerant cultivar. In addition to Al tolerance, genes in the ALMT family are also known to influence other physiological processes such as guard cell regulation, fruit quality, and seed development [102].…”
Section: Application Of Molecular Tools In Breeding For Maize Toleranmentioning
confidence: 99%
“…It is still uncertain whether our knowledge on the transporter types involved in the nutrient exchange is complete. Phosphorus (P) and C sources, for instance, might be transported, not through proton-coupled symporters alone, but also by diffusion facilitators; P could be transported via phosphatepermeable anion channels (Dreyer et al, 2012) and C could be transported in neutral form as a sugar through sugar channels of the SWEET type (Sugar Will Eventually be Exported Transporter; Chen et al, 2010) or as organic acids through channels of the ALMT type (ALuminium activated Malate Transporter; Sharma et al, 2016). In this study, we tackled this issue by evaluating, in an unbiased manner, the thermodynamic features of general transporter network models for their use in nutrient exchange in AM symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Most members of the ALMT family are not involved in Al 3+ resistance but perform other functions on different membranes [21,36]. For example, four members in Arabidopsis (AtALMT4, AtALMT6, AtALMT9 and AtALMT12) and one in barley (Hordeum vulgare L., HvALMT1) are involved in guard cell regulation.…”
Section: Almt Genes Perform Various Functions Among Plantsmentioning
confidence: 99%